Tinjauan Yuridis terhadap Nelayan Pelaku Pengeboman Ikan Diwilayah Perairan Labuhan Bajo Berdasarkan UU No 31 Tahun 2004 Hukum Lingkungan (Studi Kasus Putusan No.02/Pid.Sus/2013/Pn.Lbj) - Tito Rahmadani; Aryo Fadlian (Wajah Hukum, 2022)
The existence of laws in the life of people in a country, basically can not only be said to be an effort to regulate activities in people's lives, but can also be an effort that can change behavior and thinking in an individual or community group. Indonesia as a country surrounded by the ocean, has a lot of fishery resources that are still not explored and exploited optimally. This fishery regulation is regulated in the Law of the Republic of Indonesia No. 31 of 2004 concerning Fisheries. This research is a means for humans to discover facts, existence and develop science. Meanwhile, in this research, which is legal research, it is one of the activities based on certain systematics, methods and thoughts with the aim of being able to study and gain an understanding of the symptoms of the law, and also the path and analysis in depth regarding facts with the law which are then solved with problems derived from the symptoms of the law. The results of this study show that the criminal act of bombing fish is in accordance with what has been considered by the Judge. Fisheries crimes are caused by economic factors, weak morality, weak morals and creeds. The use of explosives used by the defendant is regulated in Ri Law No. 45 of 2009 concerning amendments to RI Law No. 31 of 2004 concerning Fisheries.